2009
DOI: 10.1073/pnas.0906429106
|View full text |Cite
|
Sign up to set email alerts
|

DNA-mediated redox signaling for transcriptional activation of SoxR

Abstract: In enteric bacteria, the cellular response to oxidative stress is activated by oxidation of the iron-sulfur clusters in SoxR, which then induces transcription of soxS, turning on a battery of defense genes. Here we demonstrate both in vitro and in cells that activation of SoxR can occur in a DNA-mediated reaction with guanine radicals, an early genomic signal of oxidative stress, serving as the oxidant. SoxR in its reduced form is found to inhibit guanine damage by repairing guanine radicals. Moreover, cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…Another possible role for the 2Fe-2S cluster of CPSF30 is to regulate oligonucleotide binding a redox-dependent manner; Fe-S clusters are emerging as key cofactors in a range of regulatory proteins. In some proteins for which the Fe-S cluster plays a regulatory role, such as the base excision repair proteins, the Fe-S cluster's DNA binding affinity is dependent on the oxidation state of the Fe-S cluster and modulated by DNA charge transfer (57)(58)(59)(60)(61)(62). In others, such as Aft2 (which also contains a structural zinc site), it is the presence or absence of the Fe-S cluster that drives DNA binding (63).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible role for the 2Fe-2S cluster of CPSF30 is to regulate oligonucleotide binding a redox-dependent manner; Fe-S clusters are emerging as key cofactors in a range of regulatory proteins. In some proteins for which the Fe-S cluster plays a regulatory role, such as the base excision repair proteins, the Fe-S cluster's DNA binding affinity is dependent on the oxidation state of the Fe-S cluster and modulated by DNA charge transfer (57)(58)(59)(60)(61)(62). In others, such as Aft2 (which also contains a structural zinc site), it is the presence or absence of the Fe-S cluster that drives DNA binding (63).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, XPD may utilize DNA-mediated CT to signal its presence and perhaps to "call off" other proteins from other repair pathways. Various DNA-binding proteins, such as those involved in repair and other DNA transactions, have been found to contain iron-sulfur domains and other redox cofactors (50)(51)(52)(53). DNAmediated signaling among DNA-binding proteins that are involved in maintaining the integrity of the genome allows a coordination of repair, transcription, and replication processes.…”
Section: Discussionmentioning
confidence: 99%
“…130 This important shift maintains the protein in an inactive state during normal conditions such that it only becomes activated when the cell experiences conditions of high oxidative stress. Proper coupling to the DNA π -stack is additionally important for this protein, as solution experiments have shown that SoxR can be activated from a distance by DNA CT. 134 Clearly, as in the case of small molecule redox probes, strong electronic coupling to the DNA π -stack is essential to produce measurable electrochemical signals. For proteins like SoxR, however, this coupling has an added level of significance, as it can actually modulate the redox character of the protein itself, significantly impacting the function of the protein in a biological context.…”
Section: Dna Ct On Surfacesmentioning
confidence: 99%